Effectiveness and safety of tumor-treating fields therapy for glioblastoma: A single-center study in a Chinese cohort - She, Lei; Gong, Xuan; Su, Lin; Liu, Chao (Frontiers in Neurology, 2023)
Objective Tumor-treating fields (TTFields) are a new therapeutic modality for patients with glioblastoma (GBM). However, studies on survival outcomes of TTFields are rarely reported in China. This study aimed to examine the clinical efficacy and safety of TTFields therapy for GBM in China. Methods A total of 93 patients with newly diagnosed GBM (ndGBM) and recurrent GBM (rGBM) were included in our study retrospectively. They were divided into two groups based on whether they used TTFields. Progression-free survival (PFS), overall survival (OS), and toxicities were assessed. Results Among the patients with ndGBM, there were 13 cases with TTFields and 39 cases with no TTFields. The median PFS was 15.3 [95% confidence interval (CI): 6.5–24.1] months and 10.6 (95% CI: 5.4–15.8) months in the two groups, respectively, with P = 0.041. The median OS was 24.8 (95% CI: 6.8–42.8) months and 18.6 (95% CI: 11.4–25.8) months, respectively, with P = 0.368. Patients with subtotal resection (STR) who used TTFields had a better PFS than those who did not (P = 0.003). Among the patients with rGBM, there were 13 cases with TTFields and 28 cases with no TTFields. The median PFS in the two groups was 8.4 (95% CI: 1.7–15.2) months and 8.0 (95% CI: 5.8–10.2) months in the two groups, respectively, with P = 0.265. The median OS was 10.6 (95% CI: 4.8–16.4) months and 13.3 (95% CI: 11.0–15.6) months, respectively, with P = 0.655. A total of 21 patients (21/26, 80.8%) with TTFields developed dermatological adverse events (dAEs). All the dAEs could be resolved or controlled. Conclusion TTFields therapy is a safe and effective treatment for ndGBM, especially in patients with STR. However, it may not improve survival in patients with rGBM.